The Effectiveness of Public Service Digitalization Policies in Promoting Social Inclusion - Hugo Abejundio; Samantha Samantha (IHSA Institute, 2026)
The digitalization of public services has become a central strategy for governments to enhance efficiency, transparency, and accessibility. However, the extent to which these policies promote social inclusion remains a critical concern, particularly in the context of persistent digital inequalities. This study aims to analyze the effectiveness of public service digitalization policies in fostering social inclusion, with a focus on accessibility, usability, coverage, equity, and user satisfaction. A mixed-methods approach is employed, combining quantitative data collected through surveys of digital service users with qualitative insights obtained from interviews with government officials and citizens, as well as analysis of relevant policy documents. The findings indicate that while digitalization has significantly improved service efficiency and expanded access, its impact on social inclusion is uneven. Urban populations and individuals with higher levels of digital literacy benefit more from digital services, whereas rural communities, the elderly, low-income groups, and people with disabilities continue to face substantial barriers. Key challenges identified include limited internet infrastructure, low digital literacy, resistance to technology, policy implementation gaps, and budget constraints. The study concludes that the effectiveness of digitalization policies is moderate and highly dependent on supporting conditions such as infrastructure availability, user capability, and inclusive policy design. To enhance social inclusion, the study recommends strengthening digital literacy programs, expanding internet access in underserved areas, designing user-friendly and accessible systems, and maintaining offline service alternatives. Ultimately, the research emphasizes that digital transformation in public services must be accompanied by inclusive strategies to ensure that its benefits are equitably distributed across all segments of society.